Yield Gap Analysis of Toria (Brassica campestris) through Front Line Demonstrations in Kandhamal District of Odisha - D. V. Singh , S. K. Mukhi and M. R. Mohapatra, (Indian Journal of Extension Education, 2016)
The present study was carried out at Krishi Vigyan Kendra, Kandhamal to know the yield gaps between improved packageand practices (IP) under Front Line Demonstration (FLD) and farmer's practice (FP) of toria crop. Yield attributes of bothdemonstration and farmers' practice were recorded and their yield gap, technology gap, extension gap and technologyindex were analyzed. The average five years data revealed that an average yield of demonstrated plot was obtained 10.01q/ha over local check (6.55 q/ha.) and there is an increase in average productivity by 52.97 per cent. On an averagetechnology gap was recorded to be 1.99 q/ha. While average extension gap was observed to be 3.46 q/ha. Averagetechnology index was recorded as 16.63 per cent. The average cost benefit ratio was 2.55 under demonstration, while itwas 1.75 under control plots. The trend of technology gap reflected the farmer's cooperation in carrying outdemonstrations with encouraging results in subsequent years. By conducting front line demonstration of proventechnologies, yield potential of rapeseed-mustard crop could be enhanced with increase in the income level of the farmingcommunity.